Early diagnosis and management of inseparable conjoint twins. A low-middle-income country experience - Aditiawarman (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS Conjoined twins have captivated mankind for centuries due to the rarity of this birth type; nonetheless, physicians have constantly encountered difficulties in dealing with conjoined twins. Early diagnosis of conjoined twins during prenatal examination is critical for ascertaining the prognosis of the fetus, guiding parental counseling over appropriate courses of action, and potentially enabling the termination of the pregnancy. First-trimester ultrasonography and MRI are complementary modalities in determining the diagnosis and prognosis of conjoined twins in early pregnancy.   ABSTRACT Objectives: To discuss the crucial early diagnosis of conjoined twins to determine the type and prognosis. Case Report: A 27-year-old woman was referred to the type A referral hospital with suspicion of congenital abnormalities at 17 weeks of pregnancy. Ultrasound results showed intrauterine monochorionic monoamniotic twins with babies fused on their heads to the urogenital part. The MRI showed a craniopagus, suspected meningomyelocele, and severe bilateral hydronephrosis in the second baby. Due to non-separable cases and a bad prognosis for the fetus, the pregnancy was terminated using misoprostol induction and inserting a balloon catheter. The fetus was born weighing 400 g and 20 cm in length. Conjoined twins obtained the rostral type: a fused head with two faces, a fused thorax until the lower abdomen with one umbilicus, and two pairs of hands and feet. The diagnosis of conjoint twins becomes a problem in early pregnancy, mostly in developing countries. Early diagnosis of conjoined twins during prenatal examination is critical for ascertaining the prognosis of the fetus, guiding parental counseling over appropriate courses of action, and potentially enabling the termination of the pregnancy to prevent maternal stress and complications. Conclusion: Conjoined twins should be identified as soon as feasible to establish the best course of management for both mother and fetus. Ultrasonography and MRI are modalities for determining the diagnosis and prognosis of conjoined twins.